Enhanced Late Na and Ca Currents as Effective Antiarrhythmic Drug Targets - Karagueuzian, Hrayr; Pezhouman, Arash; Angelini, Marina; Olcese, Riccardo (Frontiers in Pharmacology, 2017)
While recent advances clarified the molecular and cellular modes of action of antiarrhythmic drugs (AADs), their link to suppression of dynamical arrhythmia mechanisms remains only partially understood. The current classifications of AADs (Classes 1, III, and IV) rely on blocking peak Na, K and L-type calcium currents (ICa,L), with Class II with dominant beta receptor blocking activity and Class V including drugs with diverse classes of actions. The discovery that the calcium and redox sensor, cardiac Ca/calmodulin-dependent protein kinase II (CaMKII) enhances both the late Na (INa-L) and the late ICa-L in patients at high risk of VT/VF provided a new and a rational AAD target. Pathological rise of either or both of INa-L and late ICa,L are demonstrated to promote cellular early afterdepolarizations (EADs) and EAD-mediated triggered activity that initiates VT/VF in remodeled hearts. Selective inhibition of the INa-L without affecting their peak transients with the highly specific prototype drug, GS-96 suppresses these EAD-mediated VT/VFs. As in the case of INa-L, selective inhibition of the late ICa,L without affecting its peak with the prototype drug, roscovitine suppressed oxidative EAD-mediated VT/VF. These findings indicate that specific blockers of the late inward currents without affecting their peaks (gating modifiers), offer a new and effective AAD class action i.e., “Class VI.” The development of safe drugs with selective Class VI actions provides a rational and effective approach to treat VT/VF particularly in cardiac conditions associated with enhanced CaMKII activity such as heart failure.